Pain and Suffering: Finding Solace in a Vital Church - Ilo, Stan Chu (Concilium, 2025)
This essay argues that Christians find solace in pain through relational resilience within inclusive communities of faith - what I call "vital churches." These communities serve as spaces of accompaniment, restoration, and agentic freedom. Across Africa and beyond, such churches are rising as counter-logics to suffering, enacting solidarity with the wounded, the poor, and the marginalized. Through these healing bonds, vital churches inspire critical hope and model a renewed future grounded in love, relational resilience, and support.